Entrepreneurial competencies, business coaching, and business success among Malaysian women micro-entrepreneurs / Mohd Mahfudz Idris - Idris, Mohd Mahfudz (2021)
Women micro-entrepreneurs are the essential developers of microenterprises and significant business drivers in developing nations, including Malaysia. Having successful women micro-entrepreneurs may contribute tremendously to economic progress through the generation of income and job availability. However, although having a crucial role in the economy, the number of successful Malaysian women micro-entrepreneurs is still low, and they are underperformed; thus, their business success is still vague. Women micro-entrepreneurs should be competent in executing their tasks to succeed in business. Simultaneously, business coaching plays a vital role in improving entrepreneurial competencies, as these competencies influence business success. Therefore, this study’s main objectives are to examine the domains of entrepreneurial competencies and the role of perceived usefulness of business coaching in influencing business success. The research philosophy of this study is pragmatist epistemology. This study’s design is descriptive and correlational, applying the quantitative research method. The respondents of this study are 261 women micro-entrepreneurs who attended business coaching conducted by Amanah Ikhtiar Malaysia nationwide, in which the samples were selected using a cluster sampling technique. The questionnaire survey was analysed using SPSS version 22.0 and Amos version 22.0, in which this study performed descriptive analysis and Structural Equation Modelling. This study found that more than half of the women micro-entrepreneurs fall under the age group of thirty-one to forty years old through the descriptive data analysis. This result reflects that the age group of thirty-one to forty years old is the right average group for the highest business commitment. Furthermore, women micro-entrepreneurs under this age range are more energetic, highly aspirated, and have a long business journey. These findings are further confirmed through the regression analysis. The analysis found that commitment, conceptual, opportunity, and relationship competencies significantly influence business success. Through the moderation analysis in determining the moderating effect of perceived usefulness of business coaching on the relationship among domains of entrepreneurial competencies, i.e., strategic, commitment, conceptual, opportunity, organising and leading, relationship, personal, and technical competencies with business success, it is found that strategic, commitment, conceptual, and relationship competencies have moderating effect. Thus, the perceived usefulness of business coaching plays a role in the relationships among the four domains of entrepreneurial competencies with business success. This study can expand the literature and body of knowledge in understanding women micro-entrepreneurs’ business success, enormously expanding the literature on domains of entrepreneurial competencies that are exclusively and mutually relevant for women micro-entrepreneurs by understanding the direct effect of entrepreneurial competencies and moderating effect of perceived usefulness of business coaching.